Epilepsy diagnostic and treatment needs identified with a collaborative database involving tertiary centers in France. (1st April 2016) - Chipaux, Mathilde; Szurhaj, William; Vercueil, Laurent; Milh, Mathieu; Villeneuve, Nathalie; Cances, Claude; Auvin, Stéphane; Chassagnon, Serge; Napuri, Sylvia; Allaire, Catherine; Derambure, Philippe; Marchal, Cécile; et al.
Summary: Objective: To obtain perspective on epilepsy in patients referred to tertiary centers in France, and describe etiology, epilepsy syndromes, and identify factors of drug resistance and comorbidities. Methods: We performed a cross‐sectional analysis of the characteristics of 5, 794 pediatric and adult patients with epilepsy included in a collaborative database in France between 2007 and 2013. Comparisons between groups used Student's t ‐test or Fisher's exact test for binary or categorical variables. Factors associated with drug resistance and intellectual disability were evaluated in multi‐adjusted logistic regression models. Results: Mean age at inclusion was 17.9 years; children accounted for 67%. Epilepsy was unclassified in 20% of patients, and etiology was unknown in 65%, including those with idiopathic epilepsies. Etiologies differed significantly in adult‐ when compared to pediatric‐onset epilepsy; however, among focal structural epilepsies, mesial temporal lobe epilepsy with hippocampal sclerosis began as often in the pediatric as in adult age range. Drug resistance concerned 53% of 4, 210 patients evaluable for seizure control and was highest in progressive myoclonic epilepsy (89%), metabolic diseases (84%), focal cortical dysplasia (70%), other cortical malformations (69%), and mesial temporal lobe epilepsy with hippocampal sclerosis (67%). Fifty‐nine percent of patients with focal structural epilepsy and 69% with epileptic encephalopathies were drug resistant; however, 40–50% of patients with West syndrome and epileptic encephalopathy with continuous spike‐and‐waves during sleep were seizure‐free. Ages at onset in infancy and in young adults shared the highest risk of drug resistance. Epilepsy onset in infancy comprised the highest risk of intellectual disability, whereas specific cognitive impairment affected 36% of children with idiopathic focal epilepsy. Significance: Our study provides a snapshot on epilepsy in patients referred to tertiary centers and discloses needs for diagnosis and treatment. Large databases help identify patients with rare conditions that could benefit from specific prospective studies.